2015
DOI: 10.1200/jco.2015.33.3_suppl.46
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of brain metastasis in esophageal cancer.

Abstract: 46 Background: Brain metastasis in oesophageal cancer is a rare but often fatal complication. In previous studies the incidence has ranged from 1.4% - 13% with the largest studies from China and Japan that have been retrospectively based over fifteen to twenty years. (Ogawa K, Toita T, Sueyama H. Brain metastases from esophageal carcinoma: natural history, prognostic factors, and outcome. Cancer. 2002 Feb 1;94(3):759-64.) With improving diagnostic techniques and differing histology of oesophageal cancer from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…After evaluating 157 esophageal cancer patients with brain metastases, Ai and associates found that adenocarcinoma was associated with a higher risk for developing brain metastases, whereas squamous cell cancer was associated with a lower risk of brain metastases [ 9 ]. Other studies also reported that the most common histological type accompanied by brain metastases was adenocarcinoma [ 6 , 12 ]. The mechanism behind the increased risk of brain metastases in esophageal adenocarcinoma may be related to the overexpression of HER2 [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 98%
“…After evaluating 157 esophageal cancer patients with brain metastases, Ai and associates found that adenocarcinoma was associated with a higher risk for developing brain metastases, whereas squamous cell cancer was associated with a lower risk of brain metastases [ 9 ]. Other studies also reported that the most common histological type accompanied by brain metastases was adenocarcinoma [ 6 , 12 ]. The mechanism behind the increased risk of brain metastases in esophageal adenocarcinoma may be related to the overexpression of HER2 [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 98%